Peirce and deleuze in the “protoplasm of philosophy”: Triadic relations and habit as pragmatic concepts - Cardoso, Hélio Rebello [UNESP] (Addleton Academic Publishers, 2019)
This article reviews G. Deleuze’s (1925–1995) relationship to C.S. Peirce (1839–1914) played out in the former’s lectures held and books published between 1981 and 1985, both dedicated to the signs of cinema. It focuses on the interchange of their respective concepts of (triadic) relations and habit, revealing a higher resonance from Deleuze’s thought towards Peirce’s pragmatism than the literature usually admits. It faces an embarrassing issue: Deleuze never mentions pragmatism in his studies on semiotic concerning the classification of the signs of cinema, to which Peirce, along with H. Bergson (1859–1941), are the main references. Reversely, when Deleuze unsystematically approaches pragmatism he makes no mention of Peirce at all. In the final part, the article provides a portrait of the early and recent reception of Peirce in France to insert the argument into the historical context. Ultimately, this article exposes and inspects eight limited, but close, conceptual correspondences between Deleuze’s and Peirce’s thought with respect to: triadic relations and reality; triadic relations and meaning; irreducibility of triadic relations; triadic relations and the changing form of time; habits and triadic relations; habits and human beings; habits and nature; and the principle of habit-taking.
Keywords: Deleuze; Habit; Peirce; Pragmatism; Relation; Triadic